Biochemical Characterization of Mannanase from Newly Isolated Acinetobacter sp. KUB-ST1-1 and its Hydrolysate Containing Mannooligosaccharides: Potential as Applied Prebiotic for Pet Food - Sintuprapa, Wilawan; Alaiphol, Aonchuma; Nitisinprasert, Sunee; Zhou, Zhemin; Moonmangmee, Somporn (Applied Science and Engineering Progress, 2025)
The β-mannanase enzyme derived from isolated Acinetobacter sp. KUB-ST1-1 was studied for its potential for mannooligosaccharide production. Extracellular mannanase from Acinetobacter sp. KUB-ST1-1, cultured in nutrient broth with 0.5% (w/v) locust bean gum, was purified using ultrafiltration, anion exchange chromatography, and cation exchange chromatography. The enzyme, with a molecular weight of 57 kDa, had high activity in a 50 mM phosphate buffer at pH 6.0 and was stable from pH 4.0 to 7.0. It had high-temperature stability at 40 °C and 50 °C for up to 18 h. This enzyme was highly active toward konjac and galactomannan, especially with locust bean gum and copra meal. The hydrolysis products consisted mainly of the 2 and 3 units of mannooligosaccharide. The mannooligosaccharide exhibited prebiotic properties by promoting increased growth of some beneficial lactic acid bacteria. Furthermore, the defatted copra meal hydrolysate had considerable resistance to pepsin, trypsin, and bile salts under simulated gastrointestinal conditions for dogs. These characteristics highlighted the enzyme's excellent properties and suggested its potential as a promising candidate for applications in the food and bio-industries, particularly in pet food production.